Cu-Al-O powders prepared from zeolite precursors by combinated treatment of ball milling and heating - Kosanović, Cleo (Array, 2008)
Abstract: By applying combination of mechanochemical and thermal treatment important materials that could be used in sensor and semiconductor technology as well in catalysis are obtained. High energy ball milling was applied to prepare powder samples by treating mixture consisted a) of Cu and ammonium exchanged zeolite A and b) of CuO and ammonium exchanged zeolite A. According to X-ray powder diffraction the mechanical treatment resulted in mixture of amorphous phase and low size crystal particles. After 3 h of milling the samples were isothermally treated at the appropriate temperature yielding crystalline mixtures with a dominant phase of CuAlO2. Thermal treatment of Cu-exchanged zeolite A resulted in a crystalline sample with dominant phase CuAl2O4